Luminescence properties of Sm3+ ions doped aluminium barium phosphate glasses - Chanthima, Natthakridta; Kiwsakunkarn, Nuchjaree; Kaewkhao, Jakrapong (Interdisciplinary Research Review, 2018)
In this paper, the physical, optical and photoluminescence properties of alkali metals on Sm3+ ions doped aluminium barium phosphate (R2O-Al2O3-BaO-P2O5, where R = Li, N, K) at 1 mol% Sm2O3 have been investigated. These glasses were prepared by melt quenching technique at 1200 °C. The density and molar volume of Sm3+ ions were calculated. The absorption spectra consist of nine peaks corresponded the transitions from the 6H5/2 ground state to various excited energy levels. Photoluminescence spectra shows four prominent emission bands corresponding to the 4G5/2→6HJ (J = 5/2, 7/2, 9/2 and 11/2) transitions and the intensities of all band are enhanced by Sm3+ ion content.